Creating the improvised moment - Ronen, Yotam (Jazz Research Journal, 2024)
In the summer of 2023, a dancer, a saxophone player, and a bass player got into a room and recorded ‘Rega’—an improvised conversation on the concept of time. Now, several months after its publication, this article aims to reflect on the process of the planning, creation, and final publication of ‘Rega’ utilizing the perspective of care. Care, this article argues, is both a necessary ethical praxis, and one that creates unique improvisational conversations within the improvised moment. Bringing together in-depth descriptive accounts of the performance itself together with contemporary literature on improvisation, this article is intended as an invitation for others to consider care within their own improvisational endeavours, from initial planning to final execution.